Gene-based immunotherapy of skin cancers - Sun, Yuansheng; Schadendorf, Dirk (Cancers of the Skin, 2002)
Skin cancers continue to present a major therapeutic challenge to physicians. Recent advances in molecular genetics and improved understanding of immune responses to tumors have generated an interest in using gene-based immunotherapy for treating these malignancies. Two major forms of gene-based immunotherapy are currently being investigated. One focuses on genetic modification of some target cell populations of the host using immunostimulatory genes such as cytokines, in order to improve tumor immunogenicity and antitumor responses; the other is genetic immunization with the genes coding for melanoma-associated antigens recognized by cytotoxic T cells. This paper reviews these novel strategies and summarizes the most recent data recorded in either experimental studies or clinical trials.
Gesehen am 11.11.2020